2022
DOI: 10.3389/fenvs.2022.964230
|View full text |Cite
|
Sign up to set email alerts
|

Lolium multiflorum germination and growth affected by virgin, naturally, and artificially aged high-density polyethylene microplastic and leachates

Abstract: With the detection of microplastics in soil, coupled with the various sources continuously contributing to its delivery to and distribution in soils, understanding the effects of microplastics on plants are necessary. Plastics discarded in the environment continually degrade into micro- and nano-sizes, subsequently leaching hazardous chemicals with time. Not only time but also environmental factors related to the climate of the area where the plastic is degrading will contribute to the breakdown process. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Similar to the results of the present study, Esterhuizen et al (2022) found the inhibition of root and shoot growth to be comparable, irrespective of exposure to particles or leachates of the same plastic. Esterhuizen et al (2022), however, also looked at artificially aged (high-density) PE fragments, finding the difference between new and aged microplastics and leachates to indicate that the aging of the plastic significantly decreases the toxicological effect on root and shoot growth. These results, as well as those conducted by others within their group (Pflugmacher et al 2020(Pflugmacher et al , 2021a(Pflugmacher et al , 2021b, indicate a correlation between aging and a decrease in phytotoxicity, conflicting the results of the present study, where the suppression of root and shoot biomass was similar, regardless of whether the exposure was to pristine or aged films of the same polymer.…”
Section: Responses Of L Perenne To Different Types Sizes and Age Of P...supporting
confidence: 91%
See 4 more Smart Citations
“…Similar to the results of the present study, Esterhuizen et al (2022) found the inhibition of root and shoot growth to be comparable, irrespective of exposure to particles or leachates of the same plastic. Esterhuizen et al (2022), however, also looked at artificially aged (high-density) PE fragments, finding the difference between new and aged microplastics and leachates to indicate that the aging of the plastic significantly decreases the toxicological effect on root and shoot growth. These results, as well as those conducted by others within their group (Pflugmacher et al 2020(Pflugmacher et al , 2021a(Pflugmacher et al , 2021b, indicate a correlation between aging and a decrease in phytotoxicity, conflicting the results of the present study, where the suppression of root and shoot biomass was similar, regardless of whether the exposure was to pristine or aged films of the same polymer.…”
Section: Responses Of L Perenne To Different Types Sizes and Age Of P...supporting
confidence: 91%
“…Concentrations used to leach additives from plastics, simultaneously producing "aged" plastics, has varied remarkably among published studies (e.g. from 2 g L −1 (Lee et al 2022) to 100 g L −1 (Esterhuizen et al 2022); these values represent the mass of plastic per litre of water), but has been primarily based on measured concentrations of environmental plastic pollution in the field (Coffin et al 2018;Bridson et al 2021). The environmental aging of MP cannot be fully simulated by mechanical stress alone, as photodegradation also plays a significant role (Liu et al 2021).…”
Section: Experimental Design and Setupmentioning
confidence: 99%
See 3 more Smart Citations